(untitled) (Revista Apotheke, 2022)
The purpose of this article is to present the narratives of three women teachers/educators and their production of presences as black female educators. These are stories that dig up memories and bring the urgency to exist and take this enchantment to their pedagogical practices crossed by the five senses. These stories intersect and can be read/ lived in various territories of our country, within any school, especially public schools, where bodies are still concentrated at the margins of the places said to be of power. These experiences intersect in singular questions: in what ways are black bodies seen in spaces, called educators? How do these bodies create epistemes from their experiences and encounters? Is there room for these encounters in education? We trawled our way through the findings of our master’s research and, crossing our personal stories and the motivations that drove us to continue working in education, we created a dialogue with reflections and positions based mainly on the theories of Grada Kilomba, Bell Hooks, and Nilma Lino Gomes, researchers that also bring teachings from their experiences to theorize and practice anti-racist actions in formal and non-formal education spaces, joining the experience of Conceição Evaristo as a fertile meeting place for equals, understanding and systematization of personal and collective knowledge.